Hybrid Procedures. Opening Doors for Surgeon and Cardiologist Close Collaboration - Juan-Migu; Juan-Migu; José-Luis Zunzunegui; José-Luis Zunzunegui; Ramón Pérez-Caballero; Ramón Pérez-Caballero; Ana Pita; Ana Pita; Carlos Pardo; Carlos Pardo; Corazón Calle; Corazón Calle; et al. (Frontiers Media S.A., 2021)
Background: Collaboration between cardiac surgeons and cardiologists can offer interventions that each specialist may not be able to offer on their own. This type of collaboration has been demonstrated with the hybrid Stage I in patients with hypoplastic heart syndrome. Since that time, a hybrid approach to cardiac interventions has been expanded to an incredible variety of potential indications.Methods: Seventy-one patients were scheduled for a hybrid procedure along 8 years. This was defined as close collaboration between surgeon and cardiologist working together in the same room, either cath-lab (27 patients) or theater (44 patients).Results: Six groups were arbitrarily defined. A: vascular cut-down in the cath-lab (27 neonates); B: bilateral banding (plus ductal stent) in hypoplastic left heart syndrome or alike (15 children); C: perventricular closure of muscular ventricular septal defect (10 cases); D: balloon/stenting of pulmonary branches along with major surgical procedure (12 kids); E: surgical implantation of Melody valve (six patients) and others (F, one case). Two complications were recorded: left ventricular free wall puncture and previous conduit tearing. Both drawbacks were successfully sort out under cardiopulmonary by-pass.Conclusion: Surgeon and cardiologist partnership can succeed where their isolated endeavors are not enough. Hybrid procedures keep on spreading, overcoming initial expectations. As a bridge to biventricular repair or transplant, bilateral banding plus ductal stent sounds interesting. Novel indications can be classified into different groups. Hybrid procedures are not complication-free.